(untitled) (European Journal of Pure and Applied Mathematics, 2025)
The radio labeling problem has numerous applications including military communications, satellite communication, mobile networks, and internet technology. This issue is NP-hard. A rapid algorithm for determining the upper bound of the radio number of a given graph is proposed in this paper. The superior performance of the proposed algorithm is attributed to Saha and Panigrahi (2012). The superior performance of the proposed algorithm in terms of CPU time can be attributed to Badr and Mousa(2019). The mathematical model demonstrates that the proposed algorithm exhibits superior performance in terms of both the maximum number of radios and CPU time. The proposed algorithm is ultimately assessed using a collection of networks that possess a range of characteristics. Besides that, we present the application of such algorithm in cryptography.